PERSEPSI PENGELOLA KEUANGAN DESA DALAM MEWUJUDKAN TRANSPARANSI DAN AKUNTABILITAS KEUANGAN DESA DI KECAMATAN MAWASANGKA KABUPATEN BUTON TENGAH - Masud, Arifuddin; Safaruddin, Safaruddin; Falziah, Falziah (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
ABSTRACTÂ This research aims to determine the perception of village financial managers in realizing the financial transparency and accountability village in the district Mawasangka Central Buton regency. The scope of this study is limited to the transparency and accountability of financial management of villages in the district Mawasangka Buton District Central views of the readiness of human resources in the financial management of villages of the village head, village secretary, treasurer villages and other village as the financial manager of the village, as well as the Consultative Body Village. The method used is descriptive statistical methods.The results of this study indicate that the village as financial manager village has an excellent perception in achieving transparency and financial accountability village in the district Mawasangka Central Buton regency. It is seen from the percentage of the overall tendency of respondents answers on the questionnaire statements are given as percentages namely for 85.94% of the variable transparency and accountability for the variables of 87.11% each showed excellent interpretation.Â Keywords: Perception, Financial operators village, Transparency, Accountability.